PENGARUH LEVERAGE, UKURAN PERUSAHAAN DAN LIKUIDITAS TERHADAP KEBIJAKAN DIVIDEN: Studi Kasus Perusahaan Sektor Industri Barang Konsumsi - Wafa Nabila, - (2019)
This study aims to examine the effect of Leverage proxied with Debt to Equity Ratio (DER), Firm Size proxied by Logarithm Natural Asset and Liquidity Proxied with Current Ratio (CR) toward Dividend Policy proxied by Dividend Payout Ratio (DPR). Population in this study are manufacture companies of consumer goods industry sector listed in Indonesia Stock Exchange (IDX) 20142017. The sampling techniques used in this study is purposive sampling and obtained 17 consumer goods industry sector companies with a research period of four years to obtain 64 units of samples. Data analysis was done using Microsoft Excel 2016 and hypothesis testing in this research using Data Panel Regression Analysis with E-Views 9.0 program and significance level of 2.5%. The result of the research shows that (1) leverage (DER) has no effect on dividend policy (DPR), (2) firm size (SIZE) has no effect on dividend policy (DPR), (3) liquidity (CR) has no effect on dividend policy (DPR).